Needle flame resistant polyimide film and preparation method thereof

By using phenoxyphosphazene flame retardant and inorganic filler in polyimide films, the protective film and thermal barriers are formed, and the problem of surface burning through the polyimide film in needle flame test is solved, achieving high Improved flame resistance and mechanical properties.

CN118956152BActive Publication Date: 2025-01-14TIANJIN JIANUOYUAN ELECTRONICS TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411450355.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing polyimide films are burned through during needle flame tests, which do not meet the requirements of high flame resistance.

Method used

Using phenoxyphosphazene flame retardants and inorganic fillers, the protective film is formed by adding phosphorus, nitrogen, silicon flame retardants, silicon dioxide, aluminum trioxide and other inorganic fillers to the polyimide film. and thermal barriers, block oxygen supply and heat conduction, and promote the carbonization process.

Benefits of technology

It significantly improves the needle flame resistance of the polyimide film, can withstand needle flame combustion for at least 70 seconds without burning, and the limit oxygen index reaches 48.6-64.2, enhancing mechanical properties and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of polyimide films, in particular to a needle flame resistant polyimide film and a preparation method thereof. A needle flame resistant polyimide film comprises the following raw materials: diamine, dianhydride, flame retardant, inorganic filler, solvent; the flame retardant is at least one of phenoxyphosphazene flame retardant and diphenyl phosphate; the inorganic filler is at least one of silicon dioxide and aluminum oxide; by weight, the amount of the flame retardant is 5-15% of the total weight of dianhydride and diamine, and the amount of the inorganic filler is 3-15% of the total weight of dianhydride and diamine. The obtained polyimide film can achieve the effect of no perforation and no cracks after a 70s needle flame test; the limiting oxygen index can reach 48.6-64.2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polyimide films, and in particular to a needle flame resistant polyimide film and a preparation method thereof. Background Art

[0002] Polyimide film is an organic polymer film containing imide rings in the main chain of the molecule. Its unique structure gives the film excellent mechanical properties, excellent insulation properties, and superb high / low temperature resistance; it is widely used in various fields.

[0003] In recent years, with the continuous development of the microelectronics industry and the new energy industry, the application fields of polyimide films have been further expanded. Polyimide films have been used in emerging fields such as 5G communications, consumer electronics, flexible displays, and new energy vehicles.

[0004] With the application of polyimide film in microelectronics (such as consumer electronics) and new energy (such as lithium batteries), higher requirements are placed on the performance of polyimide film, especially its flame resistance. The needle flame test simulates and evaluates the fire hazard of parts / materials of electrical and electronic equipment due to leakage tracking fault current, overheating of components or parts, poor contact, etc.

[0005] The Chinese patent with application number 201910350656.9 discloses a flame-retardant polyimide resin and a preparation method thereof. A flame-retardant polyimide resin is prepared from the following raw materials in parts by weight: 10-20 parts of diamine; 30-100 parts of dianhydride; 3-5 parts of flame-retardant modifier; 1-2 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-phosphoethane. Its limiting oxygen index can reach 65-80. However, the applicant found that according to GB / T 5169.5-2020 "Fire Hazard Test for Electrical and Electronic Products Part 5: Test Flame Needle Flame Test Method Apparatus, Confirmation Test Method and Guidelines", a needle flame test was carried out on it. After burning for 60s, it can be observed that the surface of the film was burned through and failed. The applicant believes that it is extremely important to improve the needle flame resistance of polyimide film. Summary of the invention

[0006] In order to improve the needle flame resistance of a polyimide film, the present application provides a needle flame resistant polyimide film and a preparation method thereof.

[0007] In a first aspect, the present application provides a needle flame resistant polyimide film, which adopts the following technical solution.

[0008] A needle flame resistant polyimide film comprises the following raw materials: diamine, dianhydride, flame retardant, inorganic filler, solvent;

[0009] By weight, the flame retardant is used in an amount of 5-15% of the total weight of the dianhydride and the diamine, and the inorganic filler is used in an amount of 3-15% of the total weight of the dianhydride and the diamine;

[0010] The flame retardant is at least one of a phosphorus flame retardant, a nitrogen flame retardant, a metal hydroxide, and a silicon flame retardant;

[0011] The phosphorus-based flame retardant includes at least one of a phenoxyphosphazene flame retardant and a diphenyl phosphate;

[0012] The preparation method of the phenoxyphosphazene flame retardant is:

[0013] Dissolve hexachlorocyclotriphosphazene in a solvent, then add anhydrous potassium carbonate and mix, then add p-nitrophenol solution, heat and reflux at 50-60° C. for 18-20 hours; after the reaction is completed, filter, wash, dry and recrystallize to obtain a phenoxyphosphazene flame retardant.

[0014] In some specific embodiments, the flame retardant is any one of phosphorus flame retardant, nitrogen flame retardant, metal hydroxide, and silicon flame retardant. In some specific embodiments, the flame retardant is a combination of two or more of phosphorus flame retardant, nitrogen flame retardant, metal hydroxide, and silicon flame retardant, such as in some specific embodiments, the flame retardant is a combination of phosphorus flame retardant and nitrogen flame retardant; in some specific embodiments, the flame retardant is a combination of phosphorus flame retardant, metal hydroxide, and silicon flame retardant.

[0015] By adopting the above technical solution, phenoxyphosphazene flame retardants will undergo a decomposition reaction when heated, and this decomposition process is an endothermic process. When it is added to a polyimide film and exposed to a high temperature environment such as a needle flame test, the decomposition of the phenoxyphosphazene flame retardant will absorb a large amount of heat, thereby reducing the temperature of the film surface and slowing down the combustion reaction. When phenoxyphosphazene flame retardants are decomposed by heat, they will generate acidic substances such as phosphoric acid, metaphosphoric acid and polyphosphoric acid. These acidic substances can form a non-volatile protective film on the surface of the film. This protective film can isolate the air (especially oxygen) from direct contact with the film, thereby blocking the oxygen supply required for combustion and improving the needle flame resistance of the film. During the decomposition process, phenoxyphosphazene flame retardants will also release non-combustible gases such as carbon dioxide, ammonia, nitrogen and water vapor. The release of these gases can dilute the oxygen concentration around the material and reduce the concentration of combustible gases, thereby further inhibiting the combustion reaction. During the combustion process, phenoxyphosphazene flame retardants will generate free radicals such as PO·, which can combine with active free radicals such as H· and HO· in the flame, thereby interrupting the free radical chain reaction and inhibiting the spread and expansion of the flame. This effect of terminating the chain reaction is crucial to improving the needle flame resistance of the material. Phenoxyphosphazene flame retardants can also promote the carbonization process of the material at high temperatures. Carbonization is a physical and chemical change process in which the material loses volatile components and forms a stable carbonaceous structure at high temperatures. This carbonaceous structure has high thermal stability and flame retardancy, which can further improve the needle flame resistance of the material.

[0016] Inorganic fillers can significantly improve the thermal stability of polyimide films, allowing them to maintain structural integrity in high-temperature environments and not easily decompose or melt. The microstructure formed in the polyimide film can also act as a thermal barrier, hindering the rapid conduction of heat. In the needle flame test, this helps to mitigate the thermal shock of the flame on the internal structure of the film and reduce the risk of failure of the film due to high temperature. In addition, the addition of inorganic fillers can also significantly improve the mechanical properties of polyimide films, including tensile strength, flexural strength and toughness. This makes the film more resistant to the mechanical impact and damage of the flame in the needle flame test.

[0017] The polyimide film obtained in the present application can withstand needle flame combustion for at least 70 seconds without burning or cracking.

[0018] Furthermore, the preparation method of the phenoxyphosphazene flame retardant is:

[0019] Dissolve hexachlorocyclotriphosphazene in a solvent, then add anhydrous potassium carbonate and mix, then add p-nitrophenol solution, heat and reflux at 50-60° C. for 18-20 hours; after the reaction is completed, filter, wash, dry and recrystallize to obtain a phenoxyphosphazene flame retardant.

[0020] Furthermore, the weight ratio of the hexachlorocyclotriphosphazene to p-nitrophenol is 1:(3-5).

[0021] By adopting the above technical scheme, the flame retardant obtained by the reaction of hexachlorocyclotriphosphazene with p-nitrophenol contains a specific nitro functional group, which further improves the flame retardant performance of the flame retardant.

[0022] Furthermore, the phenoxyphosphazene flame retardant is grafted with a transition metal sulfide, and the preparation method thereof is as follows:

[0023] 1) Surface modification of transition metal sulfides;

[0024] The transition metal sulfide is subjected to surface treatment to introduce hydroxyl groups on the surface of the transition metal sulfide; the hydroxyl transition metal sulfide is then dispersed in a dispersion, an aminosilane coupling agent is added, and an aminosilane coupling agent is reacted to graft the aminosilane coupling agent onto the transition metal sulfide to obtain a modified transition metal sulfide;

[0025] 2) Grafting reaction

[0026] The modified transition metal sulfide and the phenoxyphosphazene flame retardant are mixed in a solvent, reacted at 60-100° C., washed and dried after the reaction, and the phenoxyphosphazene flame retardant grafted with the transition metal sulfide is obtained.

[0027] Furthermore, the weight ratio of the transition metal sulfide to hexachlorocyclotriphosphazene is 1:(6-9).

[0028] By adopting the above technical solution, transition metal sulfide is grafted on the flame retardant. Transition metal sulfide is a new material with a graphene-like layered structure and a unique lamellar structure, which can effectively reduce heat conduction and promote the formation of a dense carbon layer. When the transition metal sulfide is grafted on the flame retardant, in a needle flame environment, when the flame retardant decomposes, the carbonization process of the film at high temperature is promoted to form a stable carbonaceous structure. This carbonaceous structure has high thermal stability and flame retardancy, and can further improve the needle flame resistance of the material.

[0029] Furthermore, the weight ratio of the flame retardant to the inorganic filler is 1:(0.5-1.5).

[0030] Furthermore, the inorganic filler is at least one of silicon dioxide, aluminum oxide, calcium oxide, boron nitride and molybdenum disulfide.

[0031] In some specific embodiments, the inorganic filler is any one of silicon dioxide, aluminum oxide, calcium oxide, boron nitride, and molybdenum disulfide. In some specific embodiments, the inorganic filler is a combination of two or more of silicon dioxide, aluminum oxide, calcium oxide, boron nitride, and molybdenum disulfide. For example, in some specific embodiments, the inorganic filler is a combination of silicon dioxide and aluminum oxide. In some specific embodiments, the inorganic filler is a combination of silicon dioxide, calcium oxide, and boron nitride.

[0032] Furthermore, the inorganic filler is silicon dioxide and aluminum oxide in a weight ratio of (2-5):1, the particle size of the silicon dioxide is (1-2) μm, and the particle size of the aluminum oxide is (4-5) μm.

[0033] By adopting the above technical solution, the particle gradation of silicon dioxide and aluminum oxide is limited. Within the gradation range defined in the present application, the inorganic filler is uniformly and densely filled in the film, which helps to improve the needle flame resistance and mechanical properties of the film.

[0034] Further, the diamine is any one or more of 4,4-diaminodiphenyl ether, m-phenylenediamine, and 4,4'-diaminodiphenylmethane;

[0035] The dianhydride is any one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 4,4'-oxydiphthalic anhydride;

[0036] The molar ratio of the diamine to the dianhydride is 1:(0.990-1.005).

[0037] In some specific embodiments, the diamine is 4,4-diaminodiphenyl ether, and the dianhydride is pyromellitic dianhydride.

[0038] In some specific embodiments, the diamine is a mixture of 4,4-diaminodiphenyl ether and m-phenylenediamine; and the dianhydride is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride.

[0039] In some specific embodiments, the diamine is a mixture of 4,4-diaminodiphenyl ether, m-phenylenediamine, and 4,4'-diaminodiphenylmethane; and the dianhydride is a mixture of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 4,4'-oxydiphthalic anhydride.

[0040] In a second aspect, the present application provides a method for preparing a needle flame resistant polyimide film, which adopts the following technical solution.

[0041] A method for preparing a needle flame resistant polyimide film comprises the following steps:

[0042] S1. The flame retardant is dispersed in 1 / 5 of the solvent to obtain a flame retardant dispersion;

[0043] S2. The inorganic filler is dispersed in 1 / 5 of the solvent to obtain an inorganic filler dispersion;

[0044] S3. The diamine is added to the remaining solvent and stirred to completely dissolve it to form an amine solution;

[0045] S4. Add the flame retardant dispersion to the amine solution and stir continuously;

[0046] S5. The inorganic filler dispersion is added to the amine solution with continuous stirring;

[0047] S6. Heat to 30-60°C, add dianhydride in small amounts and multiple times to react to form a polyamic acid resin solution:

[0048] S7. After the viscosity of the polyamic acid resin meets the requirements, vacuum defoaming is performed for (6-8) hours;

[0049] S8. The defoamed polyamic acid resin solution is subjected to film casting to obtain a polyimide film.

[0050] Furthermore, the viscosity of the polyamic acid resin in S7 is 150,000-300,000 centipoise.

[0051] In summary, this application has the following beneficial effects:

[0052] When the flame retardant defined in the present application is compounded with an inorganic filler, the flame retardant will undergo a decomposition reaction when heated. The decomposition process absorbs heat, and the decomposition will produce acidic substances such as phosphoric acid, metaphosphoric acid and polyphosphoric acid, as well as non-combustible gases such as carbon dioxide, ammonia, nitrogen and water vapor. These acidic substances can form a non-volatile protective film on the surface of the film. This protective film can isolate the direct contact between air and the film, thereby blocking the oxygen supply required for combustion; the release of non-combustible gas can dilute the oxygen concentration around the material and reduce the concentration of combustible gas, thereby further inhibiting the combustion reaction. Inorganic fillers can significantly improve the thermal stability of polyimide film, so that it maintains structural integrity under high temperature environment and is not prone to thermal decomposition or melting. The microstructure formed in the polyimide film can also act as a thermal barrier to hinder the rapid conduction of heat. In the needle flame test, this helps to slow down the thermal shock of the flame on the internal structure of the film and reduce the risk of failure of the film due to high temperature. Flame retardants and inorganic fillers work together in terms of flame retardancy and preventing damage to the film due to combustion, greatly improving the needle flame resistance of the film. The obtained polyimide film can achieve the effect of no perforation and no crack after a 70s needle flame test; the limiting oxygen index can reach 48.6-64.2.

[0053] The flame retardant obtained by reacting hexachlorocyclotriphosphazene with p-nitrophenol contains a specific nitro functional group, which further improves the flame retardant performance of the flame retardant.

[0054] Transition metal sulfides are grafted onto flame retardants. When the flame retardant decomposes in a needle flame environment, the carbonization process of the film at high temperature is promoted to form a stable carbonaceous structure. This carbonaceous structure has high thermal stability and flame retardancy, and can further improve the needle flame resistance of the material. DETAILED DESCRIPTION

[0055] The present application is further described in detail below with reference to the embodiments.

[0056] Raw materials and intermediate preparation examples

[0057] raw material

[0058] The raw materials in the examples of this application can be obtained from the market:

[0059] Diamine, 4,4-diaminodiphenyl ether, purity ≧99%;

[0060] Dianhydride, pyromellitic dianhydride, purity ≧99%;

[0061] Solvent, N,N-dimethylformamide;

[0062] Hexachlorocyclotriphosphazene, purity ≥ 99%;

[0063] Anhydrous potassium carbonate, analytical grade;

[0064] Acetone, analytical grade;

[0065] p-Nitrophenol, analytical grade;

[0066] Dimethylformamide, analytical grade;

[0067] Transition metal sulfides, MoS2 nanosheets.

[0068] Preparation Example

[0069] Preparation Example 1

[0070] A phenoxyphosphazene flame retardant and a preparation method thereof:

[0071] 1 kg of hexachlorocyclotriphosphazene was dissolved in 8 L of acetone solvent, and then 1.9 kg of anhydrous potassium carbonate was added to mix to obtain a mixed solution; 4 kg of p-nitrophenol was dissolved in 11 L of acetone to obtain a p-nitrophenol solution, and the p-nitrophenol solution was slowly added dropwise to the mixed solution within 0.5 h, and then heated to 55° C. with stirring, and refluxed for 18 h; after the reaction, the obtained product was washed with water, acetone, methanol and ether in turn, and then vacuum dried at 60° C. for 12 h to obtain a white powder, and finally recrystallized twice with dimethylformamide to obtain white crystals, which are phenoxyphosphazene flame retardants.

[0072] Preparation Example 2

[0073] Different from Preparation Example 1, in Preparation Example 2, 3 kg of p-nitrophenol was dissolved in 9 L of acetone to obtain a p-nitrophenol solution.

[0074] Preparation Example 3

[0075] Different from Preparation Example 1, in Preparation Example 2, 5 kg of p-nitrophenol was dissolved in 14 L of acetone to obtain a p-nitrophenol solution.

[0076] Preparation Example 4

[0077] Different from Preparation Example 1, in Preparation Example 2, 6 kg of p-nitrophenol was dissolved in 174 L of acetone to obtain a p-nitrophenol solution.

[0078] Preparation Example 5

[0079] The phenoxyphosphazene flame retardant grafted with transition metal sulfide has a preparation method as follows:

[0080] 1) Surface modification of transition metal sulfides;

[0081] 1 kg of transition metal sulfide is completely immersed in mercaptoethanol, ultrasonically treated for 15 minutes, and then freeze-dried to introduce hydroxyl groups on the surface of the transition metal sulfide; then the hydroxy transition metal sulfide is dispersed in ethanol, and then 0.5 kg of aminosilane coupling agent 3-aminopropyltriethoxysilane is added to react, and the aminosilane coupling agent is grafted on the transition metal sulfide to obtain a modified transition metal sulfide;

[0082] 2) Grafting reaction

[0083] The modified transition metal sulfide and 6 kg of the phenoxyphosphazene flame retardant obtained in Preparation Example 1 were mixed in a dimethylformamide solvent and reacted at 80° C. After the reaction, the mixture was washed and dried to obtain the phenoxyphosphazene flame retardant grafted with the transition metal sulfide.

[0084] Preparation Example 6

[0085] Different from Preparation Example 5, the amount of phenoxyphosphazene flame retardant used in Preparation Example 6 is 9 kg.

[0086] Preparation Example 7

[0087] Different from Preparation Example 5, the amount of phenoxyphosphazene flame retardant used in Preparation Example 7 is 5 kg.

[0088] Example

[0089] Examples 1-3

[0090] A method for preparing a needle flame resistant polyimide film comprises the following steps:

[0091] S1. The solvent was divided into three parts according to 1:1:3, and the flame retardant was dispersed in 1 / 5 of the solvent according to the raw material ratio in Table 1 to obtain a flame retardant dispersion;

[0092] S2. The inorganic filler is dispersed in 1 / 5 of the solvent to obtain an inorganic filler dispersion;

[0093] S3. The diamine is added to the remaining solvent and stirred to completely dissolve it to form an amine solution;

[0094] S4. Add the flame retardant dispersion to the amine solution and stir continuously;

[0095] S5. The inorganic filler dispersion is added to the amine solution with continuous stirring;

[0096] S6. Heat to 45°C, add dianhydride three times, and react to form a polyamic acid resin solution:

[0097] S7. When the viscosity of the polyamic acid resin is 150,000 centipoise, vacuum defoaming is performed for 7h;

[0098] S8. The defoamed polyamic acid resin solution is cast into a film and imidized at 300° C. for 10 minutes to obtain a polyimide film.

[0099] Table 1 Raw material ratio table (kg)

[0100]

[0101] The inorganic filler is silicon dioxide with a particle size of (1-2) μm and aluminum oxide with a particle size of (4-5) μm in a weight ratio of 3:1; and the flame retardant is diphenyl phosphate.

[0102] Embodiment 4-7

[0103] Different from Example 2, the flame retardants in Examples 4-7 come from Preparation Examples 1-4, respectively.

[0104] Examples 8-10

[0105] Different from Example 2, the flame retardants in Examples 8-10 come from Preparation Examples 5-7, respectively.

[0106] Embodiment 11

[0107] Different from Example 8, the inorganic filler in Example 11 is silicon dioxide with a particle size of (1-2) μm and aluminum oxide with a particle size of (4-5) μm in a weight ratio of 2:1.

[0108] Example 12

[0109] Different from Example 8, the inorganic filler in Example 11 is silicon dioxide with a particle size of (1-2) μm and aluminum oxide with a particle size of (4-5) μm in a weight ratio of 5:1.

[0110] Embodiment 13

[0111] Different from Example 8, the inorganic filler in Example 13 is silicon dioxide with a particle size of (1-2) μm and aluminum oxide with a particle size of (4-5) μm in a weight ratio of 1:3.

[0112] Embodiment 14

[0113] Different from Example 8, the inorganic filler in Example 14 is silicon dioxide with a particle size of (4-5) μm and aluminum oxide with a particle size of (1-2) μm in a weight ratio of 3:1.

[0114] Comparative Example

[0115] Comparative Example 1

[0116] Different from Example 4, in Comparative Example 1, an equal amount of flame retardant is used to replace the inorganic filler.

[0117] Comparative Example 2

[0118] Different from Example 4, in Comparative Example 2, the flame retardant is replaced by an equal amount of inorganic filler.

[0119] Comparative Example 3

[0120] Different from Example 4, in Comparative Example 3, the flame retardant is 50.00 kg and the inorganic filler is 8.50 kg.

[0121] Performance Testing

[0122] The properties of the polyimide films obtained in the examples and comparative examples were tested as follows. The test results are shown in Table 2.

[0123] Needle flame resistance test: refer to the method in "Fire hazard test for electric and electronic products Part 5: Test flame needle flame test method apparatus, confirmation test method and guidance" GB / T 5169.5-2020 to observe the combustion of the polyimide film after 70s;

[0124] Limiting oxygen index test: refer to the method in "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test" GB / T2406.2-2009 to detect the limiting oxygen index of polyimide film;

[0125] Tensile strength test: refer to the method in "Electrical Insulating Films Part 2: Test Methods" GB / T 13542.2-2021 to test the tensile strength of polyimide film.

[0126] Table 2 Performance test results

[0127]

[0128] Combining Examples 1-14 with Comparative Examples 1-3 and Table 2, it can be seen that the needle flame resistance and limiting oxygen index of the polyimide film obtained in Examples 1-14 are better than those of Comparative Examples 1-3, and there is no obvious difference in tensile strength between Examples 1-14 and Comparative Example 1, which shows that the polyimide film prepared in the present application has better comprehensive performance in needle flame resistance test, flame retardancy and mechanical properties, and meets the application requirements in electronic components.

[0129] Combining Example 4 with Comparative Examples 1-3 and Table 2, it can be seen that Example 4 uses flame retardants and inorganic fillers in the ratio specified in the present application, Comparative Example 1 uses only flame retardants, Comparative Example 2 uses only inorganic fillers, and the ratio of the amount of flame retardants and inorganic fillers in Comparative Example 3 exceeds the range specified in the present application. The needle flame resistance and limiting oxygen index of the polyimide film obtained in Example 4 are better than those of Comparative Examples 1-3, which indicates that the use of flame retardants and inorganic fillers in the ratio specified in the present application can effectively improve the needle flame resistance test performance and flame retardant properties of the polyimide film. This may be because the flame retardant of the present application will undergo a decomposition reaction when heated, and the decomposition process absorbs heat. The decomposition will produce acidic substances such as phosphoric acid, metaphosphoric acid and polyphosphoric acid, as well as non-combustible gases such as carbon dioxide, ammonia, nitrogen and water vapor. These acidic substances can form a non-volatile protective film on the surface of the film. This protective film can isolate the direct contact between air and the film, thereby blocking the oxygen supply required for combustion; the release of non-combustible gas can dilute the oxygen concentration around the material and reduce the concentration of combustible gas, thereby further inhibiting the combustion reaction. Inorganic fillers can significantly improve the thermal stability of polyimide film, so that it maintains structural integrity under high temperature environment and is not prone to thermal decomposition or melting. The microstructure formed in the polyimide film can also act as a thermal barrier to hinder the rapid conduction of heat. In the needle flame test, this helps to slow down the thermal shock of the flame on the internal structure of the film and reduce the risk of failure of the film due to high temperature. Flame retardants and inorganic fillers work together in terms of flame retardancy and preventing damage to the film due to combustion, greatly improving the needle flame resistance of the film.

[0130] In combination with Examples 4-10 and Table 2, it can be seen that the needle flame resistance of the films obtained in Examples 8-10 is better than that of Examples 4-7, which shows that the grafting modification of phenoxyphosphazene flame retardants with transition metal sulfides can effectively improve the needle flame resistance of polyimide films. This may be because when the transition metal sulfide is grafted onto the flame retardant, the flame retardant decomposes in the needle flame environment, which promotes the carbonization process of the film at high temperature to form a stable carbonaceous structure. This carbonaceous structure has high thermal stability and flame retardancy, and can further improve the needle flame resistance of the material.

[0131] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A needle flame resistant polyimide film, characterized in that: The method comprises the following raw materials: diamine, dianhydride, flame retardant, inorganic filler and solvent; the molar ratio of the diamine to the dianhydride is 1:(0.990-1.005); By weight, the flame retardant is used in an amount of 5-15% of the total weight of the dianhydride and the diamine, and the inorganic filler is used in an amount of 3-15% of the total weight of the dianhydride and the diamine; The flame retardant is a phosphorus-based flame retardant, and the phosphorus-based flame retardant is a phenoxyphosphazene flame retardant; The preparation method of the phenoxyphosphazene flame retardant is: Dissolving hexachlorocyclotriphosphazene in a solvent, then adding anhydrous potassium carbonate to mix, then adding p-nitrophenol solution, heating and reflux reaction at 50-60° C. for 18-20 hours; after the reaction is completed, filtering, washing, drying, and recrystallizing to obtain a phenoxyphosphazene flame retardant; The phenoxyphosphazene flame retardant is grafted with a transition metal sulfide, and the grafting method is as follows: 1) Surface modification of transition metal sulfides The transition metal sulfide is subjected to surface treatment, wherein the transition metal sulfide is a molybdenum disulfide nanosheet, and a hydroxyl group is introduced on the surface of the transition metal sulfide; the hydroxyl transition metal sulfide is then dispersed in a dispersion, an aminosilane coupling agent is added, and an aminosilane coupling agent is reacted to graft the aminosilane coupling agent onto the transition metal sulfide to obtain a modified transition metal sulfide; 2) Grafting reaction The modified transition metal sulfide and the phenoxyphosphazene flame retardant are mixed in a solvent, reacted at 60-100° C., washed and dried after the reaction, and the phenoxyphosphazene flame retardant grafted with the transition metal sulfide is obtained; The inorganic filler is silicon dioxide and aluminum oxide in a weight ratio of (2-5):1, the particle size of the silicon dioxide is (1-2) μm, and the particle size of the aluminum oxide is (4-5) μm.

2. The needle flame resistant polyimide film according to claim 1, characterized in that: The weight ratio of the hexachlorocyclotriphosphazene to p-nitrophenol is 1:(3-5).

3. The needle flame resistant polyimide film according to claim 1, characterized in that: The weight ratio of the transition metal sulfide to hexachlorocyclotriphosphazene is 1:(6-9).

4. The needle flame resistant polyimide film according to claim 1, characterized in that: The weight ratio of the flame retardant to the inorganic filler is 1:(0.5-1.5).

5. The needle flame resistant polyimide film according to claim 1, characterized in that: The diamine is any one or more of 4,4-diaminodiphenyl ether, m-phenylenediamine, and 4,4'-diaminodiphenylmethane; The dianhydride is any one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 4,4'-oxydiphthalic anhydride.

6. A method for preparing a needle flame resistant polyimide film according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. The flame retardant is dispersed in 1 / 5 of the solvent to obtain a flame retardant dispersion; S2. The inorganic filler is dispersed in 1 / 5 of the solvent to obtain an inorganic filler dispersion; S3. The diamine is added to the remaining solvent and stirred to completely dissolve it to form an amine solution; S4. Add the flame retardant dispersion to the amine solution and stir continuously; S5. The inorganic filler dispersion is added to the amine solution with continuous stirring; S6. Heat to 30-60°C, add dianhydride in small amounts and multiple times to react to form a polyamic acid resin solution: S7. After the viscosity of the polyamic acid resin reaches 150,000-300,000 centipoise, it is subjected to vacuum defoaming for 6-8h; S8. The defoamed polyamic acid resin solution is subjected to film casting to obtain a polyimide film.

Citation Information

Patent Citations

  • Flame-retardant polyimide resin and preparation method thereof

    CN110128822A

  • Polymer supershort fiber reinforced fuel cell proton exchange membrane and its preparing method

    CN101071873A

  • Fuel battery proton exchange film keeping humidity via mineral fiber and its making method

    CN101087028A